Surgery First and Aligners: A Case Report Combining In-House Surgical Guides and Pre-Adapted Titanium Plates - Mohammedreza Sefidroodi; Inleel Lundgård Shino; Stratos Vassis; Karen Eich Hammer; Kasper Dahl Kristensen; Thomas Klit Pedersen; Sven Erik Nørholt; Jytte Buhl (Applied Sciences)
Continuous advancements in technology have made it possible to integrate clear aligner therapy (CAT) with orthognathic surgery. This case report presents a novel, individually-planned workflow, combining CAT with a surgery-first orthognathic approach (SFOA) in collaborating with engineers for an in-house production of surgical guides and customized titanium plates. The patient was evaluated subjectively, using the Oral Health-Related Quality of Life-14 (OHIP-14) questionnaire and Orthognathic Quality of Life questionnaire (OQLQ), and objectively with the Peer Assessment Rating (PAR) index. The patient displayed the planned occlusal relationship with no report of discomfort in the temporomandibular joint (TMJ) or post-surgical complications. The surgical and occlusal outcomes have remained consistent and stable after debonding. A decreased score was reported in both questionnaires and the PAR after treatment, thereby indicating improvements in both subjective and objective evaluations. This case report demonstrates that with proper individual planning, satisfactory subjective and objective outcomes can be achieved when combining SFOA with CAT.